An entrepreneurial paradox: the moderating effect of the external environment. Issue 2 (3rd May 2016) - Kim, Hwan-Jin; Kim, Byung-Keun
Abstract : Although entrepreneurial orientation (EO) has been shown to play a key role in increasing firm performance (FP), the effects of EO have been extremely oversimplified. The plethora of empirical studies on EO and FP suggest that the EO–FP relationship is linearly positive regardless of the amount of EO investment. The results show that EO increases FP at the bounded level (i.e. an inverted U-shape). We argue that the excessive use of EO, organisational incapability and institutional constraints may contribute to the non-linearity of such effects. We also find that environmental dynamism has no significant effect. Further, contrary to the normative contention, we find that environmental hostility has a negative effect on the EO–FP relationship. The effect of environmental hostility on EO may vary depending on various factors such as firm size, resources, and institutional settings. We present prescriptive implications to practitioners on the antecedent conditions for EO practices.